Grade 12 teachers' attitude towards mass-media transmitted educational supplements - Mokgatlhe, Phefo L. (Welkom: Central University of Technology, Free State, 2000)
The purpose of this research was to investigate the essence of Grade 12 teachers' attitude towards the use of Mass-Media Educational Supplements, to textbooks and teachers as well. Firstly, the study sought to examine Grade 12 teachers' use ofMass-Media in their lessons. Secondly, the study sought to determine problems Grade 12 teachers experience when they apply Mass-Media in their lessons. Lastly, the study sought to determine the cause of problems for Grade 12 teachers when applying Mass-Media. Data were collected from one school in Thabong (Welkom). Two instruments were used to collect the data. The first instrument was the questionnaire which collected primary data, and the second instrument was the interview which collected secondary data to complement the primary data collected through the questionnaires. The results have revealed that Grade 12 teachers do in fact, have a positive attitude towards having to use Mass-Media Educational Supplements. The problem lies with lack of resources at schools, and also the time clashes at school with the time for example on which The Learning Channel is being aired. This study therefore, recommends that problems with regard to the time- table and lack of resources be addressed from a higher level than the school level, and also that Mass-Media supplements being in schools, should be centrally co-ordinated. They should be just left as a loose canon for individual school to decide on themselves what to do with it.
Thesis
Keywords: Mass media; Audio-visual materials